2022
DOI: 10.1108/jadee-07-2021-0177
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 lockdown on the economic situation and food security of rural households in India

Abstract: PurposeThe purpose of the study is to understand what impact the first COVID-19 lockdown in 2020 had on the income and food security of rural households in India and whether it differed across socioeconomic factors. Moreover, the study assesses the needs of rural households and determines whether they had received adequate support services during the lockdown.Design/methodology/approachThe study adopted a repeated-measures quantitative survey design with 1,319 rural women from 16 states of India and conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…The results showed that 14% of rural households have food security, and 52.5% need urgent assistance to struggle with inappropriate food insecurity conditions. This finding is consistent with the results of other studies ( 19 , 25 , 38 ). In developing countries, most of the livelihoods of rural households come from the agricultural sector ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results showed that 14% of rural households have food security, and 52.5% need urgent assistance to struggle with inappropriate food insecurity conditions. This finding is consistent with the results of other studies ( 19 , 25 , 38 ). In developing countries, most of the livelihoods of rural households come from the agricultural sector ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 94%
“…In other words, if the household head has a full-time job, less likely to experience a complete decline in income during the COVID-19 pandemic. Previous studies have confirmed the household head's employment status as a determinant of household's food security studies ( 38 , 66 , 67 ). Households with the unemployed head of households having either no fixed income or no income at all are more likely to have food insecurity ( 68 ).…”
Section: Discussionmentioning
confidence: 73%
“…This, in turn, adversely affected household income and, presumably, subsistence food production. These findings reinforce those of other studies on the impacts of the pandemic in rural areas of India (Jaacks et al, 2021;V. Suresh et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Varshney et al (2021) analyzed the impact of India's COVID-19 social assistance package using direct cash transfer and appreciated that emergency relief packages were delivered with lower transaction costs, minimal leakages, and in a timely manner. The food consumption pattern has changed towards subsidized staple foods in rural households due to enhanced vulnerability (Suresh et al, 2022). To overcome the challenges of COVID-19 pandemic, there was an immediate need for cash and food relief among the rural households (Sukhwani et al, 2020).…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%